An institution of dismissal from the police service as a consequence of disciplinary penalty − selected issues - Kapusta, Monika (Acta Universitatis Lodziensis. Folia Iuridica, 2016)
The purpose of this paper is to present the institution of dismissal from the police service. Deliberations presented in this paper have been limited to strictly selected and described issues. This includes a description of the disciplinary proceedings in the police and essence of the dismissal from the police service. Moreover, there are some examples of behavior that justifies the use of this penalty. Attention is also paid to the consequences of dismissal from the police service.